Effect of Demonetization on the Intermediaries of the Supply Chain of Fast Moving Consumer Goods - Kiran, Manglani (SFIMAR Research Review, 2016)
Demonetization process that started in the last phase of the calendar year 2016 bottlenecked the entire usual free flow of goods and services, as the demand in the market retrenched due to truncated expenditures by the consumers, which in turn affected retailers, wholesalers, stockists, distributors and finally the gamut of FMCG companies. It must be noted that supply chain management includes coordination and collaboration with channel partners, which may be suppliers, intermediaries, third-party service providers, or customers. Supply chain management integrates supply and demand management within and across companies.